Learning Methods in the Book Ta’lim al-Muta’allim by Az-Zarnuji: A Study of Classical Islamic Educational Thought - Yudhiarti, Ndaru Putri; tis'ina, Nur arofah; Rusydiana, Itsna (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2025)
The book Ta’lim al-Muta’allim by Az-Zarnuji remains a foundational text in the realm of Islamic education. This classical work offers a comprehensive discussion of ethical, spiritual, and methodological aspects of the learning process in Islam. The present study is motivated by the need for Islamic pedagogical models that go beyond cognitive development and also emphasize character formation and proper student conduct. The objective of this research is to explore the educational methods presented in Ta’lim al-Muta’allim and analyze their relevance to contemporary Islamic education. This study employs a qualitative approach using library research methods. Data were gathered through an in-depth textual analysis of Ta’lim al-Muta’allim and supported by classical and modern Islamic educational literature. The data were analyzed thematically to identify the core values, learning strategies, and pedagogical principles emphasized by Az-Zarnuji. The findings reveal that Ta’lim al-Muta’allim promotes learning methods that begin with sincere intention, the careful selection of teachers and companions, and the cultivation of proper etiquette toward knowledge, teachers, and peers. Its learning strategies—such as i’adah (repetition), tikrar (intensive review), taammul (deep reflection), and munazharah (discussion)—show strong alignment with modern pedagogical approaches. Moreover, personal virtues such as patience, humility (tawadhu’), piety (wara’), and trust in God (tawakkul) are deemed essential for student development. This study concludes that Az-Zarnuji’s educational philosophy remains highly relevant for character-based and spiritual education in modern Islamic learning environments.